2021
DOI: 10.1111/geb.13360
|View full text |Cite
|
Sign up to set email alerts
|

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants

Abstract: Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…Moreover, temperature-related climatic factors were strongly correlated with SES-PD (Pearson's r = 0.815, p -value < 0.01), suggesting that SES-PD of the EA–ENA disjuncts may have been constrained by certain climatic conditions. A recent study revealed a negative correlation between climatic niche overlap and divergence times within the EA–ENA disjuncts, which also supports niche conservatism among those congeneric species pairs ( Yin et al., 2021 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Moreover, temperature-related climatic factors were strongly correlated with SES-PD (Pearson's r = 0.815, p -value < 0.01), suggesting that SES-PD of the EA–ENA disjuncts may have been constrained by certain climatic conditions. A recent study revealed a negative correlation between climatic niche overlap and divergence times within the EA–ENA disjuncts, which also supports niche conservatism among those congeneric species pairs ( Yin et al., 2021 ).…”
Section: Discussionsupporting
confidence: 53%
“…As modern relicts of a once widespread flora across the Northern Hemisphere, the EA–ENA disjuncts are believed to be subject to niche conservatism, which is further interpreted as evolutionary stasis ( Wen, 1999 ; Qian and Ricklefs. 2004 ; Wen et al., 2010 ; Zhang et al., 2015 ; Yin et al., 2021 ). Apart from the evolutionary stasis in terms of morphology and geographical distribution, the present study provides insights into the niche conservatism of the EA–ENA disjuncts from a phylogenetic diversity perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, if the ecological niche conservatism hypothesis was rejected, the prediction based on ENMs may be misleading and may impair the efficient management against the invasions of AIS. However, until now this hypothesis remains debated, as some studies observed stable ecological niches of AIS in space and time (e.g., Gutierrez‐Ortega et al, 2020; Holt, 1996; Liu, Wolter, et al, 2020; Pearman et al, 2008; Yin et al, 2021), while others detected considerable niche shifts (e.g., Atwater et al, 2018; Loerch et al, 2021). Additionally, niche shifts in AIS may imply that they have adaptability to novel climates in the invasion processes, and AIS with stronger niche shifts may have higher invasion risk or potential.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, ecological factors have received increasing attention as a driver of lineage diversification and speciation (e.g., Wiens et al, 2010;Peterson, 2011;Broennimann et al, 2012;Zink, 2014;Hu et al, 2016;Fei et al, 2017;Wang et al, 2017;Gutiérrez-Ortega et al, 2020;Wei et al, 2020;Benício et al, 2021;Engler et al, 2021;Yin et al, 2021). In this debate, one of the main questions is whether newly developed species or clades exhibit signs of niche conservatism or divergence (Kozak and Wiens, 2006;Peterson, 2011;Wang et al, 2017;Zhu et al, 2020;Grossman, 2021;Meirmans, 2021;Van Dijk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%